Bio-Flocculation: A Green Tool in Biorefineries for Recovering High Added-Value Compounds from Microalgae - Heredia-Martínez, Luis G.; Gutiérrez-Diánez, Alba María; Díaz-Santos, Encarnación (Phycology, 2025)
The growing demand for the sustainable production of high-value compounds, such as biofuels, lipids, and pigments like carotenoids and phycobilin, has become the subject of numerous investigations. Furthermore, this has led to the exploration of renewable methods utilizing microalgae as feedstock to mitigate the challenges associated with producing these valuable compounds. Nevertheless, despite the numerous advantages of microalgae, the development of a microalgal biorefinery that employs sustainable, environmentally friendly, and economically efficient technologies remains a necessity. To address this challenge, the bio-flocculation process, and more specifically self-flocculation, is presented as a cost-effective and energy-efficient solution. This method is as easy and effective as chemical flocculation, which is applied at an industrial scale; however, in contrast, it is sustainable and cost-effective as no costs are involved in the pre-treatment of the biomass for oil extraction or in the pre-treatment of the medium before it can be re-used. In addition, microalgae possess molecular tools that would allow the efficiency of these processes to be increased. In the present review, we summarize the microalgal harvesting technologies used, with a particular focus on bio- and self-flocculation processes, and identify the improvements that could be made to enhance the production of high-added-value compounds while simultaneously reducing costs in microalgae biorefineries.